Fresno County Young Lawyers Association 7th Annual Justice George Hopper Memorial Luncheon - Watkins, Howard::::::::: (1988)
Judge Blaine Pettitt and Fresno County Young Lawyers Association President Brad Hill shaking hands and holding Fresno County Young Lawyers Association Hon. Blaine Pettitt Mentor Award (close-up)